Mediating role of legal services in tourism development: a necessity for sustainable tourism destinations. Issue 22 (16th November 2020) - Qasim, Suhad Othman; Tumer, Mustafa; Ozturen, Ali; Kilic, Hasan
ABSTRACT: On one side the Republic of Iraq is a potential tourist destination, on the other hand, the country is synonymous with years of civil and regional disturbances. The levels of civil unrest, political instability, and widely reported cases of human right abuses in the country and the region at large, have created economic uncertainty, especially in the country's tourism sector. To this end, this study employed a survey method to investigate the impact of political/economic stability, legal services, functional local authority and accessibility to the tourism destination. Three hundred questionnaires collected from conveniently accessed respondents were administered for data analyses with the aid of IBM SPSS Statistics tool. In the study, empirical evidence of examined hypotheses was found as significant with the three factors having positive on the tourism sector development in Iraq. This investigation also offers policy directives to stakeholders of the tourism sector development in Iraq especially in the area of rendering quality legal services to protect the right of the tourists from potential human right abuses and security issues. Furthermore, the study revealed the critical roles of political and economic instability, functional local authorities, and accessibility of destination.